Detection of Rickettsia spp. in ectoparasites of cricetid rodents from Gran La Plata, Buenos Aires Province, Argentina - Melis, Mauricio Ezequiel (2022)
Rickettsia spp. are obligate intracellular Gram-negative bacteria, worldwide distributed. The genus includes more than 20 species, many of them causing a group of diseases in humans and animals known as Rickettsiosis, usually transmitted by arthropod vectors. Although in Argentina Rickettsiosis have a low prevalence, clinical cases have been reported in Gran La Plata area. Rodents are usual hosts of ectoparasites, some of which have been involved in the enzootic life cycle of rickettsial species. The aim of this work was to detect bacteria of the genus Rickettsia in fleas, mites and ticks associated with cricetids in Gran La Plata.